Influence of compaction pressure in steel composites AISI 316 reinforced with titanium carbide against wear (2016)
(Eng) In the manufactured materials with the powder metallurgy technique, it is important to analyse the different manufacturing conditions that lead to get a better behaviour of the metallic matrix composite (MMC) against the wear, since it is one of the main industry problems largely affecting part of the production sectors. In this study the stainless steel AISI 316 was selected as a matrix reinforced at 3, 6 and 9% Vol of titanium carbide (TiC). The effect of the compaction pressure (700 – 800 MPa) and the reinforcement percentage were evaluated. The sintering temperature (1200±5°C) is reached by means of the generation of an abnormal glow discharge of direct current that transfers electric energy to a gaseous medium, generating an electric discharge between the electrodes (anode and cathode, where the sample is located) in an atmosphere of H2 – N2 and with a residence time of 30 minutes. The investigation results evidence that the ceramic particles incorporation (TiC) in an austenitic steel matrix (AISI 316) demonstrates a significant improvement in the wear resistance, getting the best behaviour when the composite is compacted at 800 MPa and with a reinforcement content of 6%. In these manufacturing conditions there is a good interaction in the matrix and the reinforcement, low porosity, superior densification with the highest hardness and lowest friction coefficient.